Prevalence and patient-reported outcomes of noncommunicable skin diseases among college students in ChinaCapsule Summary - Minxue Shen, PhD; Yi Xiao, MD; Juan Su, MD; Shuang Zhao, MD; Ji Li, MD; Juan Tao, MD; Xiaojing Kang, MD; Bin Wu, MD; Shijun Shan, MD; Xiaohui Wang, MD; Xiang Chen, MD (Elsevier, 2020)
Background: The prevalence and health-related quality of life of skin disease have been understudied in adolescents. Objective: To investigate the prevalence and relevant patient-reported outcomes of noncommunicable skin diseases in college students. Methods: First-year college students from 5 universities in China were investigated in the cross-sectional study. Skin diseases were diagnosed by dermatologists in the field survey. Itch and pain, symptoms of depression and anxiety, and sleep quality were measured by validated tools. Results: A total of 28,364 students consented to participate and completed the survey. The prevalence of acne, eczema, chronic urticaria, psoriasis, and vitiligo was 10.3%, 5.8%, 2.6%, 0.16%, and 0.23%, respectively. Eczema and chronic urticaria were associated with lower health utility estimates. Most diseases, but not psoriasis and vitiligo, were associated with the symptoms of depression and sleep disturbance. Itch intensity predicted other patient-reported outcome scores better in healthy controls than in individuals with skin diseases. Sex difference in the associations of skin diseases with patient-reported outcomes was not identified. Limitations: Cross-sectional study design and limited generalizability to the nonstudent population. Conclusion: Skin diseases are associated with moderately impaired emotional well-being, sleep quality, and quality of life, partly attributable to cutaneous symptoms.